Use of the Computer Aided Design-Computer Aided Manufacturing (CAD-CAM) system with its indications, advantages and disadvantages: An integrative review (Research, Society and Development, 2024)
The introduction of CAD-CAM in dentistry has revolutionized the way dental treatments are planned, designed, and manufactured. The CAD/CAM system refers to a set of technologies used for designing and manufacturing dental prostheses, such as crowns, veneers, dentures, among other devices. CAD/CAM systems can be a useful tool in diagnosis, planning, and rehabilitative treatments. In order to present the indications, advantages, and disadvantages of CAD/CAM technology, research was conducted in the academic databases Google Scholar, Pubmed, Lilacs, and Scielo on the subject. As a conclusion, we found that this technology offers significant benefits, including greater precision, reduced treatment time for patients, and a decrease in the need for uncomfortable traditional impressions. However, the initial cost of equipment and materials may be a challenge for some dental clinics or offices.